Lack of lymphangiogenesis during breast carcinogenesis. Issue 7 (25th June 2004) - Vleugel, M M; Bos, R; van der Groep, P; Greijer, A E; Shvarts, A; Stel, H V; van der Wall, E; van Diest, P J
Abstract : Background: Recent evidence suggests that functional intratumorous lymph vessels may be absent from some human cancers. This could result from either the failure of tumours to induce lymphangiogenesis, or the collapse of lymph vessels, caused by high interstitial tumour pressure. Methods: To differentiate between these two hypotheses, paraffin wax embedded clinical specimens from normal breast (n  =  13), usual ductal hyperplasia (n  =  11), ductal carcinoma in situ (n  =  21), and invasive breast cancer (n  =  40) were compared for lymphatic and blood vessel density by immunohistochemistry with antibodies to the lymphatic endothelial hyaluronan receptor (LYVE-1) and CD31, respectively. Results: Lymph vessel density was lower than blood vessel density in normal breast tissue. Within breast lobuli, lymph vessels were absent. In premalignant lesions blood microvessel density increased, whereas no increase in lymph vessels could be seen intralesionally. In invasive cancers, lymph vessels were absent in all but a few cases, where probably some pre-existing lymph vessels remained, although blood microvessel density was once again increased. Conclusion: Unlike angiogenesis, lymphangiogenesis is absent during breast carcinogenesis. This, and not rising interstitial pressure caused by an increase in the size of lesions, explains the absence of intratumorous lymph vessels in invasive breast cancer.